Spinal hemangioblastoma with syringomyelia manifesting as neurological dysfunction progressing over the course of 17 years: A case report - Kazuya Morita; Shingo Tanaka; Sho Tamai; Mitsutoshi Nakada (Interdisciplinary Neurosurgery, 2022)
Background: Spinal hemangioblastomas (HBs) are rare spinal cord tumors that often involve syringomyelia, which induce various neurological symptoms. The timing of surgical therapy for symptomatic spinal HB that is associated with a better neurological prognosis has not yet been established. Case description: We report a case of cervical spinal HB with extensive syringomyelia. The symptoms gradually worsened to McCormick grade IV over the course of 17 years. The patient underwent preoperative endovascular therapy followed by surgical resection. Postoperative neurological function after 3 months and 1 year improved to McCormick grade III and grade II, respectively. Conclusion: This case may be the longest documented neurological dysfunction due to spinal HB with syringomyelia. Surgical treatment of spinal HB with very long-term neurological symptoms may improve neurological symptoms.